2020
DOI: 10.36021/jethe.v3i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Syllabus Tone on Student Engagement in a Wellness Course

Abstract: This study examines the impact of changing the tone of a traditional syllabus to make it more learner-centered. The researchers examined a required wellness course that serves over 8,000 students per year at a large, four-year public university in the southern United States. Concerns about student progression through programs and graduation rates had prompted a number of faculty to look into ways to increase these numbers. The investigators changed the tone of the syllabus to determine if a more learner-center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…On the other hand, a negative course climate can be detrimental to student learning . Obviously, simply using a positive tone in the syllabus is not sufficient to improve student motivation for learning . However, using a negative tone in a document that is the students’ first encounter with the course to emphasize course policies is unproductive at best.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a negative course climate can be detrimental to student learning . Obviously, simply using a positive tone in the syllabus is not sufficient to improve student motivation for learning . However, using a negative tone in a document that is the students’ first encounter with the course to emphasize course policies is unproductive at best.…”
Section: Resultsmentioning
confidence: 99%
“…22 Obviously, simply using a positive tone in the syllabus is not sufficient to improve student motivation for learning. 23 However, using a negative tone in a document that is the students' first encounter with the course to emphasize course policies is unproductive at best. Content-focused syllabi showed mostly low evidence of all the important components.…”
Section: Component Scoresmentioning
confidence: 99%
“…At the outset of each semester, students in both classroom environments participated in the same discussion regarding the potential disadvantages of personal technology use in the workplace, specifically its hindrance to interpersonal communication, concentration, and attention. Research has shown that the language used in higher education, particularly in syllabi, can impact the way students learn (Howton, et al, 2020;Kenney & Sreckovic, 2019). Therefore, the syllabus for each class stated the personal-technology-use policy governing the class, and this statement was emphasized on the first day of the course.…”
Section: Participantsmentioning
confidence: 99%